Helping coaches through the physiology and biophysics of swimming - Stager, J. (FINA Golden Coaches Clinic 2016, 2016)
Dr. Joel Stager, Director, Counsilman Center for Science of Swimming, talks about "Helping coaches through the physiology and biophysics of swimming" at the FINA Golden Coaches Clinic 2016, December 4-5th (25:52 min).